Phonological evidence for morphological complexity in English proper names - Quentin Dabouis (Anglophonia)
This paper presents the results and an analysis of a large dataset of complex English proper names such as Cambridge, Manchester or Washington, inspired by previous work on Dutch place-names (Köhnlein 2015). Those names provide new evidence that words that do not have transparent semantics may still behave phonologically as complex words. The evidence comes from a dictionary-based study of the pronunciations of over 3500 proper names in which eight phonological characteristics were found to resemble those observed in complex words (compounds or words with neutral suffixes) rather than those found in simplex words. The analysis that I propose posits that such words are indeed complex morphologically, and that this is reflected in their phonological domain structure. This internal structure is assumed to be learned through the exposure to the recurring constituents in such names and through the identification of ‘anomalous’ phonological characteristics. A possible lexical representation is proposed that involves analytic listing (Bermúdez-Otero 2012) and coindexation between the different levels of representation in a lexical entry (Jackendoff 1997, 2002).